High‐accuracy mass attenuation coefficients and X‐ray absorption spectroscopy of zinc – the first X‐ray Extended Range Technique‐like experiment in Australia. (19th July 2021) - Ekanayake, Ruwini S. K.; Chantler, Christopher T.; Sier, Daniel; Schalken, Martin J.; Illig, Alexis J.; de Jonge, Martin D.; Johannessen, Bernt; Kappen, Peter; Tran, Chanh Q.
Abstract : The first X‐ray Extended Range Technique (XERT)‐like experiment at the Australian Synchrotron measured 496 energies from 8.51 keV to 11.59 keV for zinc metal to 0.023–0.036% accuracy. Systematics are quantified. Abstract : The first X‐ray Extended Range Technique (XERT)‐like experiment at the Australian Synchrotron, Australia, is presented. In this experiment X‐ray mass attenuation coefficients are measured across an energy range including the zinc K ‐absorption edge and X‐ray absorption fine structure (XAFS). These high‐accuracy measurements are recorded at 496 energies from 8.51 keV to 11.59 keV. The XERT protocol dictates that systematic errors due to dark current nonlinearities, correction for blank measurements, full‐foil mapping to characterize the absolute value of attenuation, scattering, harmonics and roughness are measured over an extended range of experimental parameter space. This results in data for better analysis, culminating in measurement of mass attenuation coefficients across the zinc K ‐edge to 0.023–0.036% accuracy. Dark current corrections are energy‐ and structure‐dependent and the magnitude of correction reached 57% for thicker samples but was still large and significant for thin samples. Blank measurements scaled thin foil attenuation coefficients by 60–500%; and up to 90% even for thicker foils. Full‐foil mapping and characterization corrected discrepancies between foils of up to 20%, rendering the possibility of absolute measurements of attenuation. Fluorescence scattering was also a major correction. Harmonics, roughness and bandwidth were explored. The energy was calibrated using standard reference foils. These results represent the most extensive and accurate measurements of zinc which enable investigations of discrepancies between current theory and experiments. This work was almost fully automated from this first experiment at the Australian Synchrotron, greatly increasing the possibility for large‐scale studies using XERT.